Active Fractions of Methanol Crude Obtained from Acacia Seyal Gum and their Antiproliferative Effects against Human Breast Cancer Cell Lines (Global Journal of Science Frontier Research, 2020)
Abstract not found
Keywords: cytotoxicity activity; acacia seyal gum; breast cancer(MCF-7); methanol extract/fraction; and GC-MS/MS